Pengaruh Store Atmosphere terhadap Revisit Intention Konsumen di Deja Coffee & Pastry Kelapa Gading - Gabriella, Michelle; Facrureza, Dewanta (MES Management Journal, 2024)
Factors that influence someone to visit a café are not only influenced by taste but also pay attention to the store atmosphere, where consumers can feel comfortable in the café. Deja Coffee & Pastry is a business operating in the food & beverages sector which is located in Kelapa Gading. The issue experienced by Deja Espresso and Baked good is that there are numerous purchaser protests in regards to comfort connected with the store environment and the store air itself can impact the event of return to expectation in light of the customer's insight during their visit. The motivation behind this examination is to figure out how the store air impacts return to aim at Deja Espresso and Baked good Kelapa Gading connected with the issues experienced. This examination utilizes an elucidating sort of quantitative exploration. The populace in this study are buyers who have visited Deja Espresso and Baked good Kelapa Gading without removing. The inspecting procedure utilized purposive examining of 100 individuals. The information investigation procedure utilized is instrument trying which incorporates legitimacy testing and unwavering quality testing, then, at that point, old style presumption testing, speculation testing, then coefficient of assurance, The examination results show that there is a synchronous impact applied by the store environment on return to aim at Deja Espresso and Baked good Kelapa Gading, yet to some degree the inside show aspects don't impact return to aim. Ideas for Deja Espresso and Cake Kelapa Gading are to add an air diffuser to eliminate terrible fragrances, fix the hindrance between the smoking region and the non-smoking region which upsets the solace of guests.